The effect of supplementation with fresh browse of Ziziphus mauritiana or Combretum aculeatum on feed intake, nitrogen utilization and growth of grazing range sheep - Sangare, M.; Fernández Rivera, S.; Hiernaux, Pierre H.Y.; Pandey, V.S. (Springer, 2003)
The influence of 0, 60 or 120 min access to a grove of either Ziziphus mauritiana (Ziziphus) or Combretum aculeatum (Combretum) on forage intake and on the digestibility, growth and excretion of nutrients was determined using 40 Oudah rams grazing for 7 h/day on poor-quality dry season pasture in the Sahel. The effects of browse species and browsing duration (0, 30, 60 or 120 min) on the ruminal ammonia content were also evaluated using 8 mature fistulated rams. Ziziphus increased both total digestible organic matter and total dry matter intakes per (kg live weight)0.75 without decreasing herbage intake, whereas 60 or 120 min access to Combretum reduced herbage intake by 6.3% and 4.2%, respectively. The digestibility of the diet decreased (p<0.05) with the duration of access to the groves. Despite the provision of more nitrogen (N) than in the control diet, ruminal NH3-N decreased 24 h after browsing commenced. The reduced live weight gain of sheep browsing Combretum may indicate more deleterious compounds in Combretum than in Ziziphus. Ziziphus appears to have more potential than Combretum to increase sheep production in low-input crop/livestock systems.